DEVELOPMENT OF ANIMATED VIDEO BASED ON CONTEXTUAL TEACHING AND LEARNING USING ANIMAKER ON THE MATERIAL OF EQUAL AND INVERSE VALUE COMPARISON - Umi Farihah; Ita Nurafita (UNIVERSITAS MUHAMMADIYAH METRO, 2024)
The results of needs analysis show that 51% of students prefer video-based learning. The results of mathematics teacher interview show that students have difficulty in differentiating the equal and inverse value comparison materials. This study aims to describe the validity, practicality, and effectiveness of animated videos based on CTL using Animaker on equal and inverse value comparison for students grade VII at SMP Negeri 6 Jember. This study employs the R&D method with the DDD-E model approach. Six participants were recruited on a small scale and 32 participants on a large scale. The results showed that the validity of the animated video developed included the validity of the material reached the score of 98% (very valid category), and the validity of the media reached the score of 86% (very valid category). Practicality is obtained from small-scale student responses, large-scale student responses, and teacher responses, with their respective scores reaching the score of 81.4% (very practical), 89.8% (very practical), and 86% (very practical). The effectiveness is obtained from the Wilcoxon test with Sig. 0.001 where <0.05, it can be stated that there is a difference between before and after using animated video media. While the N-Gain test reached a score of 0.72 (high category), so it can be stated to be effective. It can be concluded that the animated video developed can be said to be suitable for use in learning Mathematics.